Application of International Humanitarian Law Standards in Nigeria’s Counterinsurgency Efforts - Osadare, Michael Kehinde; Olagunju, Adesewa (ABUAD Law Journal, 2025)
The application of International Humanitarian Law (IHL) in counterinsurgency operations preserves civilians and guarantees that military activities adhere to norms of humanity and legality. Insurgent organisations like Boko Haram and the Islamic State of West Africa Province (ISWAP) are responsible for the protracted conflict in Nigeria, which raises serious questions regarding suspected violations of international humanitarian law and their severe humanitarian effects. The intricacy of implementing IHL in non-international armed situations causes issues for Nigeria, as asymmetric warfare blurs the line between combatants and civilians. The study assessed Nigeria’s implementation of IHL standards in counterinsurgency activities, identified the problems, analysed current legal and institutional frameworks, and provided concrete ways to improve compliance. This research adopted a doctrinal methodology focusing on the analysis of primary and secondary sources of law. This study found that Nigeria struggles with consistently enforcing IHL despite its commitments under international treaties, such as inadequate military training, weak accountability mechanisms, and the absence of robust civilian protection strategies. Furthermore, the absenceof IHL principles within military doctrine hinders counterinsurgency operations and risks civilian safety. The study indicated that enhancing Nigeria’s legal and institutional frameworks would guarantee IHL compliance. The study recommended upgrading military training, establishing independent oversight organisations to ensure accountability, and partnering with international organisations to monitor compliance and provide assistance when necessary to address these difficulties. By aligning its counterinsurgency operations with international standards, Nigeria can reduce the challenging humanitarian implications of its internal conflicts.